Comparison of air and oily bubbles flotation kinetics of long-flame coal. (15th January 2019) - Chen, Songjiang; Tao, Xiuxiang; Wang, Shiwei; Tang, Longfei; Liu, Quanzhou; Li, Lulu
Abstract: This paper focuses on the difference in kinetics of air and oily bubbles flotation of long-flame coal. Six flotation kinetic models were taken to fit the air and oily bubbles flotation results by the software MATrix LABoratory. The findings indicated that the conventional flotation was greater than the oily-bubble flotation in flotation rate in the early stage, and these two flotation processes exhibited different variation laws in cumulative concentrate yield with flotation time. Additionally, it was found that the classical first-order model could provide an excellent fit to the experimental data for the conventional flotation, yet all the studied kinetic models showed a great deviation in fitting to oily-bubble flotation data. Consequently, an improvement for flotation kinetic models was conducted by subtracting the delay constant in the oily-bubble flotation to attain an excellent fitting. Finally, the delay constant for the oily-bubble flotation was determined to be about 0.7500 min, while the improved classical first-order model was found to give the best fit to the oily-bubble flotation data. This study may contribute to a better understanding of the oily-bubble flotation characteristics.